IMPACT OF URBAN GREEN SPACES ON AIR QUALITY (PANGEEA, 2025)
This submission analyzes how urban green spaces influence air quality and pollution levels in metropolitan areas. It discusses methodologies for measuring pollutants, and policy implications for city planning. The study emphasizes the importance of integrating environmental management with sustainable development.
Keywords: air quality; urban green spaces; pollution